Hyperspectral imaging for perioperative monitoring of microcirculatory tissue oxygenation and tissue water content in pancreatic surgery — an observational clinical pilot study - Maximilian Dietrich (BMC, 2021)
Abstract Background Hyperspectral imaging (HSI) could provide extended haemodynamic monitoring of perioperative tissue oxygenation and tissue water content to visualize effects of haemodynamic therapy and surgical trauma. The objective of this study was to assess the capacity of HSI to monitor skin microcirculation and possible relations to perioperative organ dysfunction in patients undergoing pancreatic surgery. Methods The hyperspectral imaging TIVITA® Tissue System was used to evaluate superficial tissue oxygenation (StO2), deeper layer tissue oxygenation (near-infrared perfusion index (NPI)), haemoglobin distribution (tissue haemoglobin index (THI)) and tissue water content (tissue water index (TWI)) in 25 patients undergoing pancreatic surgery. HSI parameters were measured before induction of anaesthesia (t1), after induction of anaesthesia (t2), postoperatively before anaesthesia emergence (t3), 6 h after emergence of anaesthesia (t4) and three times daily (08:00, 14:00, 20:00 ± 1 h) at the palm and the fingertips until the second postoperative day (t5–t10). Primary outcome was the correlation of HSI with perioperative organ dysfunction assessed with the perioperative change of SOFA score. Results Two hundred and fifty HSI measurements were performed in 25 patients. Anaesthetic induction led to a significant increase of tissue oxygenation parameters StO2 and NPI (t1–t2). StO2 and NPI decreased significantly from t2 until the end of surgery (t3). THI of the palm showed a strong correlation with haemoglobin levels preoperatively (t2: r = 0.83, p < 0.001) and 6 h postoperatively (t4: r = 0.71, p = 0.001) but not before anaesthesia emergence (t3: r = 0.35, p = 0.10). TWI of the palm and the fingertip rose significantly between pre- and postoperative measurements (t2–t3). Higher blood loss, syndecan level and duration of surgery were associated with a higher increase of TWI. The perioperative change of HSI parameters (∆t1–t3) did not correlate with the perioperative change of the SOFA score. Conclusion This is the first study using HSI skin measurements to visualize tissue oxygenation and tissue water content in patients undergoing pancreatic surgery. HSI was able to measure short-term changes of tissue oxygenation during anaesthetic induction and pre- to postoperatively. TWI indicated a perioperative increase of tissue water content. Perioperative use of HSI could be a useful extension of haemodynamic monitoring to assess the microcirculatory response during haemodynamic therapy and major surgery. Trial registration German Clinical Trial Register, DRKS00017313 on 5 June 2019